Cyclic Adenosine Monophosphate (cAMP)‐Dependent Phosphodiesterase Inhibition Promotes Bone Anabolism Through CD8+ T Cell Wnt‐10b Production in Mice. (31st May 2022) - Roser‐Page, Susanne; Weiss, Daiana; Vikulina, Tatyana; Yu, Mingcan; Pacifici, Roberto; Weitzmann, M. Neale
ABSTRACT: Cyclic adenosine monophosphate (cAMP)‐dependent phosphodiesterase (PDE) inhibitors such as pentoxifylline (PTX) suppress cAMP degradation and promote cAMP‐dependent signal transduction. PDE inhibitors increase bone formation and bone mass in preclinical models and are used clinically to treat psoriatic arthritis by targeting inflammatory mediators including activated T cells. T cell activation requires two signals: antigen‐dependent CD3‐activation, which stimulates cAMP production; and CD28 co‐stimulation, which downregulates cAMP‐signaling, through PDE activation. PDE‐inhibitors consequently suppress T cell activation by disrupting CD28 co‐stimulation. Interestingly, we have reported that when CD8 + T cells are activated in the absence of CD28 co‐stimulation, they secrete Wnt‐10b, a bone anabolic Wnt ligand that promotes bone formation. In the present study, we investigated whether the bone anabolic activity of the PDE‐inhibitor PTX, has an immunocentric basis, involving Wnt‐10b production by CD8 + T cells. When wild‐type (WT) mice were administered PTX, biochemical markers of both bone resorption and formation were significantly increased, with net bone gain in the axial skeleton, as quantified by micro‐computed tomography (μCT). By contrast, PTX increased only bone resorption in T cell knockout (KO) mice, causing net bone loss. Reconstituting T cell–deficient mice with WT, but not Wnt‐10b knockout (KO) CD8 + T cells, rescued bone formation and prevented bone loss. To study the role of cAMP signaling in Wnt‐10b expression, reverse‐transcription polymerase chain reaction (RT‐PCR) and luciferase‐reporter assays were performed using primary T cells. PDE inhibitors intensified Wnt‐10b promoter activity and messenger RNA (mRNA) accumulation in CD3 and CD28 activated CD8 + T cells. In contrast, inhibiting the cAMP pathway mediators protein kinase A (PKA) and cAMP response element‐binding protein (CREB), suppressed Wnt‐10b expression by T cells activated in the absence of CD28 co‐stimulation. In conclusion, the data demonstrate a key role for Wnt‐10b production by CD8 + T cells in the bone anabolic response to PDE‐inhibitors and reveal competing T cell–independent pro‐resorptive properties of PTX, which dominate under T cell–deficient conditions. Selective targeting of CD8 + T cells by PDE inhibitors may be a beneficial approach for promoting bone regeneration in osteoporotic conditions. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research. Abstract : The phosphodiesterase (PDE) inhibitor pentoxifylline (PTX) promotes bone anabolism in the vertebrae of WT mice by a mechanism involving CD8 + T‐cell production of Wnt‐10b.